An update on semen quality among young Finnish men and comparison with Danish data. (24th September 2018) - Rodprasert, W.; Virtanen, H. E.; Sadov, S.; Perheentupa, A.; Skakkebæk, N. E.; Jørgensen, N.; Toppari, J.
Abstract: Background: Finnish men used to have higher semen quality than Danish men. However, recent studies showed that semen quality in Finland has declined, but it has been relatively stable in Denmark. Objective: This study aimed to compare new data on semen quality of the young Finnish men to that of Danish men. Materials and methods: In this cross‐sectional study, 18‐ to 19‐year‐old men residing in Turku, Finland and Copenhagen, Denmark, were invited to participate in 2008–2011. Each man filled in a questionnaire, provided one semen sample and underwent andrological examination. Semen samples were analyzed according to WHO. Multiway ANOVA was used to adjust semen variables for duration of sexual abstinence and age (and time from ejaculation to the start of semen analysis for sperm motility). Results: Altogether 287 Finnish men and 873 Danish men participated in the study. The adjusted median sperm concentrations were 49 and 47 million/mL for Finnish and Danish men, respectively ( p  = 0.48). The adjusted median total sperm counts were 148 million in Finland and 146 million in Denmark ( p  = 0.87). The adjusted median percentages of morphologically normal spermatozoa were 6.9% in Finland and 6.5% in Denmark, p  = 0.27. Finnish men had higher adjusted median percentages of motile spermatozoa (A+B+C) than Danish men (80% vs. 69%, p  < 0.001). The proportion of men who had low semen quality (sperm concentration, percentage of morphologically normal spermatozoa or percentage of progressively motile spermatozoa below WHO reference limits) was lower in Finland (25.4%) than in Denmark (34.6%), p  = 0.004. Discussion: Considerable percentage of men in both countries had low semen quality. The deteriorating semen quality in Finland may result in decreasing fecundity, which is a cause of concern. Conclusion: The formerly high semen quality in Finland has converged to the lower Danish levels. Our findings demonstrate the importance of continuing surveillance of semen quality.